Efficient Multiplex Gene Repression by CRISPR-dCpf1 in Corynebacterium glutamicum - Li, Mingyue; Chen, Jiuzhou; Wang, Yu; Liu, Jiao; Huang, Jingwen; Chen, Ning; Zheng, Ping; Sun, Jibin (Frontiers in Bioengineering and Biotechnology, 2020)
Corynebacterium glutamicum is an important workhorse for industrial production of diversiform bioproducts. Multiplex control of metabolic pathway genes is crucial for maximizing biosynthesis of desired products. However, few tools for simultaneously regulating multiple genes in C. glutamicum have been reported. Here, a CRISPR-dCpf1-based multiplex gene repression system was developed for C. glutamicum. This system successfully repressed two fluorescent reporter genes simultaneously by expressing a dCpf1(E1006A, D917A) and a designed single crRNA array. To demonstrate applications of this CRISPR-dCpf1 system in metabolic engineering, we applied this system to repress four genes involved in lysine biosynthesis (gltA, pck, pgi, and hom) with a single array, which increased the lysine titer and yield for over 4.0-fold. Quantitative PCR demonstrated that transcription of all the four endogenous target genes were repressed by over 90%. Thus, the CRISPR-dCpf1 system is a simple and effective technique for multiplex gene repression in C. glutamicum and holds promise for metabolic engineering of C. glutamicum to produce valuable chemicals and fuels.